ANALISIS KESALAHAN. SISWA. DALAM PEMBUKTIAN PERNYATAAN MATEMATIKA MENGGUNAKAN INDUKSI MATEMATIKA DI SEKOLAH MENENGAH ATAS - Dea Fitriani; Halini Halini; Dede Suratman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this research is to elaborate and describe the student error in provingmathematical statements using mathematical induction and their cause. The method ofthis research is descriptive with case study. The research subject are the student of classXI MIA SMA Islam BAWARI Pontianak. Data collection tools used diagnostic tests andinterviews. Based on the data analysis, the errors under taken by student consisted ofthree types of errors, namely conceptual errors, procedural errors and technical errors.Of the three types of errors, the most common is procedural errors. The causea ofstudent errors are that students are fixated on the sample questions given, students don’tunderstand the principle of mathematical induction, the nature of multiplication ofexponents, as well as meaning and use of the assumption n = k is true. In addition,student also don’t understand what statements are proving in the induction step, theprocedure for proving the n=k+1 and manipulate algebraic expressions in the inductionstep. There is no explanation during the online learning process so that students cannotsolve problems. Students are in a hurry when writing answer from the scribble sheet tothe answer sheet.Keywords: Error, Mathematical Induction, Proving